PENGARUH MOTIVASI TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII SMP NEGERI 21 PADANG - Anggie Mutya Febria Soneta (Jurnal Edukasi dan Penelitian Matematika, 2020)
This study aims to see how the influence of motivation on mathematics learning outcomes of class VIII students of SMP Negeri 21 Padang. Motivation has a very important role in various activities, one of which is in learning activities. This type of research is a descriptive quantitative research. The approach used in this research is a correlational approach because it looks for the influence between one variable and another. The results of the analysis show that the data analysis ofithe research results obtained the ccorrelation coefficient r count > r.table (0.365> 0.2335) at a significant level of 5% and has an effect of 13%. Keywords - Descriptive Research, Learning Motivation, Learning Outcomes